Differences in Serum Triglyceride Levels Between Blood Samples Immediately Centrifuged and Those Allowed to Clot Before Centrifugation - Mariska Vacsriani; Nurul Sulviani; Irpan Efendi Rambe; Roby Pahala Januario Gultom; Meriani Herlina; Noradina Noradina; Mutiara Siahaan; Hastrina Novasari (Cattleya Darmaya Fortuna, 2026)
The pre-analytical phase is a critical stage in clinical laboratory testing because inappropriate specimen handling may affect the accuracy of laboratory results, including serum triglyceride measurements. This study aimed to determine the differences in serum triglyceride levels between blood samples that were immediately centrifuged and those allowed to clot before centrifugation. This analytical study employed a cross-sectional paired-comparison design involving 31 respondents selected using purposive sampling. Venous blood samples from each respondent were subjected to two different pre-centrifugation treatments: immediate centrifugation and clotting for approximately 20 minutes before centrifugation. Serum triglyceride levels were determined using the enzymatic colorimetric glycerol phosphate oxidase–phenol aminophenazone (GPO-PAP) method with a photometer at a wavelength of 546 nm. Data were analyzed using descriptive statistics and the Wilcoxon Signed Rank Test at a significance level of 0.05. The results showed that the mean serum triglyceride level in blood samples that were immediately centrifuged was 142 mg/dL, whereas the mean level in blood samples allowed to clot before centrifugation was 156 mg/dL. Statistical analysis revealed a significant difference between the two treatments (p < 0.001), indicating that pre-centrifugation sample handling significantly influenced serum triglyceride measurements. It can be concluded that blood samples allowed to clot before centrifugation produced significantly higher serum triglyceride levels than samples that were immediately centrifuged. Therefore, adherence to standardized pre-analytical procedures is essential to ensure the accuracy, reliability, and consistency of serum triglyceride measurements in clinical laboratory practice.